Analisis Pengelolaan Obat di Puskesmas X Provinsi Kalimantan Selatan - Nida Anisah; Sendi Lia Yunita; Ika Ratna Hidayati (State University of Gorontalo, 2023)
Drug is an important aspect that needs to be considered in health services. Proper drug management is needed so that the availability of drugs is guaranteed and the quality of drugs is maintained. The purpose of this study was to determine drug management which includes planning, requesting, receiving and storing drugs at X Health care Center. This research is a quantitative research with a descriptive observational research design, using secondary data sources LPLPO and RKO as well as primary data sources by direct observation and 13 indicators were used. The results of the analysis of indicators of conformity of items with Fornas 91.10%, accuracy of planning 18.14%, suitability of items and number of requests 105% and 37.18%, suitability of items and number of receipts 96.83%, storage according to dosage forms 99.19% , storage according to pharmacology 0%, storage in alphabetical order 98.37%, storage according to temperature 97,56%, storage of narcotics and psychotropics according to regulations 83.33%, storage of drugs not used for other storages that cause contamination 100%, arrangement paying attention to FEFO 100% , 83.33% high-alert drug storage, 88% LASA drug storage. It can be concluded that drug management at the X Health Center has met the standard in some indicators.